Retailer’s inventory-based financing with bounded advance rates: Interplay between wholesale price contract and loan menu - Yaru Dang; Junfeng Tian; Junjie Liao; Meixian Tang; Chenyu Tian (PLoS ONE, 2026)
We examine a supply chain comprising a capital-constrained retailer, a supplier, and a bank. The retailer adopts inventory-based financing with bounded advance rates (IBF-B) to procure products through wholesale price contracts offered by the supplier. The bank is viewed as a strategic decision-maker with market power over the retailer when designing a loan menu that includes interest rates and inventory advance rates. By analyzing how inventory advance rates influence the retailer’s financing decisions, we derive upper and lower bounds for these rates to balance profitability and credit risk. Furthermore, we explore the interplay between the loan menu and wholesale price contracts. For the retailer intending to borrow up to the loan limit, the highest feasible wholesale price is offered if the supplier can obtain more profits, while the bank consistently charges the highest feasible interest rate. The upper bound of inventory advance rates is offered only when it yields a positive margin; otherwise, the interior advance rate within medium range is preferred. Numerical results illustrate the value of IBF-B, the motivations of all participants, and the impact of key economic parameters on financing decisions and supply chain performance.